Gender Mainstreaming: Policies at the National and International Level - Dulal, Tulasa Devi (Journal of Population and Development, 2020)
This paper tries to highlight the existing gender mainstreaming policies and practices at national and international level, to establish a clear vision and make commitments to guide the process of gender mainstreaming and women empowerment to achieve the gender equality, justice and fundamental human rights. The advancement of the rule of law at the national and international levels is thus, essential for the protection of fundamental human rights and freedom. Nepal has an obligation to take an effective action against all such malpractices. Nepal has participated and ratified the gender policies in all Conventions and conferences. To fulfill this very obligation, it has introduced some legal provisions and made an attempt to implement them. Due to this region, Nepal has started to address the gender issues from sixth five year plan to till now. Planned efforts to improve the situation of women began during the Sixth Plan (1981- 1985) but its approach was welfare-driven. The Interim plan (2008-2011) focused the gender responsive budget and allocated the 33 percent reservation in every state structure. The constitution of Nepal 2015, article 11 (5) and (7) compromises the ability of women to independently confer citizenship to her child. Likewise, there are many domestic legal regimes existed here. The fifteenth periodic plan approach paper, 2020 emphasizes the gender equivalence in local level. Government policies are stated with high priorities for gender main streaming policies. The experience shows that ensuring the provisions of equal rights in the constitution is important, but at the same time, proper implementation of those provisions is equally important to balance the theoretical and practical gap of gender and development. The review follows the major discourses that influenced the gender mainstreaming agenda in the form of statements in women's movements, policy documents, laws, press materials, and experiential reflection and everyday narratives captured through existing research.